Kinetics behavior of methylene blue onto agricultural waste. (17th February 2018) - Sarici-Özdemir, Çiğdem; Kiliç, Fatih
ABSTRACT: In the present work, investigations on a potential use of agricultural waste for the removal of methylene blue (MB) from wastewater are presented. Adsorption kinetics of MB has been studied using reaction-based and diffusion-based models. Three kinetic models, namely pseudo-first-order, pseudo-second-order, and the Elovich are analyzed at the temperature of 298 K for the reaction-based model. The kinetic studies showed that the data were well described by the pseudo-second-order kinetic model. Intraparticle diffusion, external-film diffusion, and internal-pore diffusion models characterizing MB were obtained. The results suggested that the agricultural waste has a high potential to be used as an effective adsorbent for MB adsorption. Pseudo-first-order, pseudo-second-order, and the Elovich models were employed to describe the desorption mechanism. The experimental results showed that the pseudo-second-order equation is the best model.